MLL associates specifically with a subset of transcriptionally active target genes. - Milne, T; Dou, Y; Martin, M; Brock, H; Roeder, R; Hess, J (2005)
MLL (mixed-lineage leukemia) is a histone H3 Lys-4 specific methyltransferase that is a positive regulator of Hox expression. MLL rearrangements and amplification are common in acute lymphoid and myeloid leukemias and myelodysplastic disorders and are associated with abnormal up-regulation of Hox gene expression. Although MLL is expressed throughout hematopoiesis, Hox gene expression is sharply down-regulated during differentiation, suggesting that either the activity of MLL or its association with target promoters must be regulated. Here we show that MLL associates with actively transcribed genes but does not remain bound after transcriptional down-regulation. Surprisingly, MLL is associated not only with promoter regions but also is distributed across the entire coding regions of genes. MLL interacts with RNA polymerase II (pol II) and colocalizes with RNA pol II at a subset of actively transcribed target in vivo. Loss of function Mll results in defects in RNA pol II distribution. Together the results suggest that an intimate association between MLL and RNA pol II occurs at MLL target genes in vivo that is required for normal initiation and/or transcriptional elongation.